Incidence of autoimmune pulmonary alveolar proteinosis estimated using Poisson distribution. Issue 1 (18th March 2019) - Kitamura, Nobutaka; Ohkouchi, Shinya; Tazawa, Ryushi; Ishii, Haruyuki; Takada, Toshinori; Sakagami, Takuro; Tanaka, Takahiro; Nakata, Koh
The incidence and prevalence of autoimmune pulmonary alveolar proteinosis in Japan were previously estimated to be 0.49 and 6.2 per million, respectively. Thereafter, an increase in serological diagnosis forced a re-estimation of the incidence based on more contemporaneous data using more robust methods. Sera of 702 patients were positive for granulocyte-macrophage colony-stimulating factor autoantibody during the 2006–2016 period (group A). Of these patients, 43 were actively surveyed in Niigata prefecture (group B) for estimation of the incidence. To estimate the survival period, 103 patients (group C) were investigated retrospectively for the 1999–2017 period using restricted mean survival time. In group A, the number of patients diagnosed in each prefecture was closely correlated with the corresponding population, indicating no regional integration of onset. In group B, a total of 43 patients were diagnosed, the annual number followed a Poisson distribution and the incidence was thus estimated to be 1.65 per million. In group C, the retrospective cohort study revealed the mean survival period to be 16.1 years. Taken together, the prevalence was estimated to be 26.6 per million, indicating that the previous data for incidence and prevalence was an underestimation. The latest epidemiologic study of autoimmune pulmonary alveolar proteinosis revealed the incidence and prevalence, estimated using Poisson distribution, to be 1.65 and 26.6 per million, respectively http://ow.ly/Wyyd30n4IYP